Investigating the difference between the acute effects of consecutive and non-consecutive days of resistance exercise on the immune system - Teo, Hilary Wei Jian (2016)
This study investigated the difference between the acute effects of consecutive (C) and non- consecutive (NC) days of resistance exercise (RE) on the immune system. It was hypothesized that there would be no significant differences between the effects of C and NC days of RE on the immune cell numbers. Twenty-one recreationally active male subjects participated in a randomized, within-subject design with five sessions. They were split into two groups. One performed RE on three C days while the other did RE on three NC days in one week. C RE was determined as having ~24 hours of recovery time in between sessions and NC RE was determined as having 48-72 hours of recovery time between sessions. Blood samples were taken thrice, once immediately before the first RE session (Pre), once immediately after the third RE session (0h) and once 24h after the third RE session (24h). Leukocyte (WBC), neutrophil (NE), monocyte (MO), basophil (BA) and platelet (PLA) showed no significant interaction between time and group and no significant main effect of group. There was significant main effect of time on WBC (p < 0.001), NE (p = 0.041), BA (p = 0.006) and PLA (p < 0.001). Both groups induced similar temporal changes following multiple bouts of RE in NE, BA and PLA. There was no significant difference between the acute effects of C and NC days of RE on the immune response.